(untitled) - Miculka, Jean H. (Mason, Ohio, 2007)
Communicate with confidence! SPEAKING FOR SUCCESS teaches you essential communication skills for life and work success. Giving you an opportunity to gain hands-on experience in practicing effective speaking, handling conversations, participating in teams, and gaining confidence in delivering formal and informal presentations, this text provides you with the tools that you need to become a successful communicator.
Keywords: Public speaking